Whole Genome Analysis of Three Multi-Drug Resistant Listeria innocua and Genomic Insights Into Their Relatedness With Resistant Listeria monocytogenes - Li, Menghan; Yan, Shaofei; Fanning, Séamus; Li, Fengqin; Xu, Jin (Frontiers in Microbiology, 2021)
Listeria innocua are Gram-positive rod-shaped bacteria, which are not generally infectious as opposed to Listeria monocytogenes. However, the comparatively high genomic similarity between both along with on occasion, their coexistence in similar ecological niches may present the opportunity for resistance or virulence gene transfer. In this study, three multi-drug resistant L. innocua originally cultured from food were put forward for long-read genome sequencing. Chromosome and plasmid genomes were assembled and annotated. Analysis demonstrated that the resistant phenotypes correlated well with genotypes. Three plasmids pLI42, pLI203, pLI47-1 were identified which harbor resistance islands. Sequence alignments suggested that plasmids pLI42 and pLI203 were highly similar to a previously sequenced L. monocytogenes plasmid pLR1. Similarly, another three types of resistant gene islands were observed on chromosome, including tet(M) gene islands (transposon Tn916 orthologs), dfrG gene islands and optrA-erm(A) gene islands. All three L. innocua isolates possessed listeria pathogenicity island-4 (LIPI-4) which is linked to cases of mengitis. Further genome environment and phylogenic analysis of regions flanking LIPI-4 of L. innocua and L. monocytogenes showed that these may have common origins and with the potential to transmit from the former. Our findings raise the possible need to include both L. monocytogenes and L. innocua in food surveillance programs so as to further understanding of the origins of antimicrobial resistance and virulence markers of public health importance in L. monocytogenes.